Suksesi Kepemimpinan Nasional Secara Selektif Berjenjang: Solusi Permasalahan Sistem Pemilihan Umum di Indonesia - Fuadi, Afnan (Prodi PPKn FKIP Universitas Pamulang, 2019)
A variety of weaknesses and problems arise in the current electoral system, including high-cost political participation as well as weak leadership regeneration system. This article presents a solution to the problem through a new mechanism of leadership succession from the lowest level (neighborhood association) to the highest level (president). A literature review method is used in this study with a focus on; 1) the selection of leader by returning the principle of deliberation and consensus as a feature of Pancasila democracy; 2) the regeneration of leaders through a tiered selective system; and 3) discussion of the process of implementing leadership succession from the lowest to the highest level. Through this new concept of leadership succession, expensive political cost becomes relatively cheap, minimizing the emergence of corrupt behavior, the elected leader has a clear track record and avoid social division and conflict.